Qualitative Aspects of Biogas Production in a Small-Scale Biodigester by Anaerobic Digestion of Food Waste from University Environment - Silva, Carlos Emílio Vieira da; Marder, Munique; Hickman, Eugênia Vargas; Oliveira, Guilherme Moraes de; Konrad, Odorico (Fronteira: Journal of Social, Technological and Environmental Science, 2022)
Organic waste are materials that, in balanced natural environments, spontaneously degrade and recycle nutrients in nature's processes. The adoption of appropriate methods for the management of organic waste is essential for urban, peri-urban and rural development. The use of Small-scale biodigestion systems in urban areas and mainly in rural areas is a real alternative. Biogas is a renewable source of energy used as a substitute for natural gas and liquefied petroleum gas. From the anaerobic decomposition of different types of biomass and substrates, we have the metabolic product called biogas, a mixture of methane, carbon dioxide and small amounts of other gases such as hydrogen sulfide. The quality of the biogas generated has a direct effect on its use as an energy source, requiring a minimum fraction of CH4 for its combustion and for other processes such as the transformation of the biogas generated into biofuel, its purification to remove the portions of other gases present its necessary. This work evaluated the quality of the biogas generated in a small-scale biodigester, based on the decomposition of food waste from the university environment. A mobile laboratory analyzed the composition of the biogas generated. The results showed that this substrate and its heterogeneity has enormous potential for generating biogas with excellent amounts of methane CH4 composition minimum value was 58.46%, the maximum reached 68.41% and the average was 65.44%. Regarding the presence of CO2 within the biogas evaluated, the minimum value of CO2 was 38.02%; the maximum value was 44.39% and the average stayed in 38.55%. Hydrogen in the composition minimum value was 7.41 ppm, 13.42 ppm maximum and average of 9.63 ppm. H2S minimum value obtained was 0.0 ppm, reaching the maximum value of 249.76 ppm, with average of 138.75 ppm.